Teacher Strategies for Addressing Students’ Affective Learning Difficulties in Islamic Religious Education at School - Aldi Pratama; Saiful Bahri; Baharudin Baharudin (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
This study aims to analyze teachers' strategies in overcoming students' learning difficulties in the affective domain in Islamic Religious Education at SMP Negeri 04 Tanjung Raja. The problems found include low interest and motivation to learn, lack of discipline, poor attention, and students' difficulties in internalizing religious values into their daily behavior. This study used a descriptive qualitative method with data collection techniques in the form of interviews, observations, and documentation involving the principal, vice principal for curriculum, teachers, students, and parents. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing and verification. The results show that affective learning difficulties are influenced by internal factors, such as low learning motivation, physical fatigue, and differences in student abilities, as well as external factors, such as monotonous learning methods, limited learning facilities, and minimal family support. To overcome these problems, teachers implemented strategies such as providing motivation, individualized approaches, using varied learning methods, creating a conducive classroom atmosphere, and conducting continuous learning evaluations. These strategies contributed positively to improving students' attitudes, responsibility, and involvement in Islamic Religious Education learning.